The Implementation of Innovative Thematic Module to Improve Students Logical Thinking Ability - Widiyatmoko, Arif; Dewi, Novi Ratna; Yanitama, Arka (Unnes Science Education Journal, 2020)
The purpose of this study was to developing an innovative thematic module on basic physics course and improving students’ logical thinking ability especially in the subject of Basic Physics II. The assessment developed in this study is an inquiry-based assessment to determine the ability to think logically by the students in learning science theme "light and vision." The research’s results and discussions are a module on the theme of light and vision developed by the eligibility requirements in very decent achievement category. The results showed that 56.66% students are in the stage of formal thinking, capable of abstract thinking and can analyze the problem scientifically and then resolve the issue, to acquire knowledge based on logical reasoning. The implementation of an innovative thematic module can improve students’ logical thinking ability.